2021
DOI: 10.3389/fphar.2021.702487
|View full text |Cite
|
Sign up to set email alerts
|

Antitumor Effects of Carvacrol and Thymol: A Systematic Review

Abstract: Background: It is estimated that one in five people worldwide faces a diagnosis of a malignant neoplasm during their lifetime. Carvacrol and its isomer, thymol, are natural compounds that act against several diseases, including cancer. Thus, this systematic review aimed to examine and synthesize the knowledge on the antitumor effects of carvacrol and thymol.Methods: A systematic literature search was carried out in the PubMed, Web of Science, Scopus and Lilacs databases in April 2020 (updated in March 2021) ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
34
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(39 citation statements)
references
References 193 publications
(343 reference statements)
4
34
0
1
Order By: Relevance
“…In contrast, eight studies mentioned that a random allocation of animals was made and that investigators were blinded (n = 8, 36.36%) (Figure 3). Similar to our results, Toro et al (2019), Sampaio et al (2021), andPina et al (2021) demonstrated that preclinical studies in animals present insufficient information that Frontiers in Pharmacology frontiersin.org implies judgment of domains. In contrast, domains that include allocation and blinding of investigators are reported in most studies included in systematic reviews (Toro et al, 2019;Pina et al, 2021;Sampaio et al, 2021).…”
Section: Risk Of Bias and Quality Of Selected Studiessupporting
confidence: 89%
“…In contrast, eight studies mentioned that a random allocation of animals was made and that investigators were blinded (n = 8, 36.36%) (Figure 3). Similar to our results, Toro et al (2019), Sampaio et al (2021), andPina et al (2021) demonstrated that preclinical studies in animals present insufficient information that Frontiers in Pharmacology frontiersin.org implies judgment of domains. In contrast, domains that include allocation and blinding of investigators are reported in most studies included in systematic reviews (Toro et al, 2019;Pina et al, 2021;Sampaio et al, 2021).…”
Section: Risk Of Bias and Quality Of Selected Studiessupporting
confidence: 89%
“…DNA topoisomerase II alpha (TOP2A) is associated with more than 200 cancer categories, and more than 100 registered drugs target this protein as inhibitors or chain breakers. Cancer is characterised with out of control cell growth cycle, and inhibition of these 7 cell cycle associated genes that already have a range of anticancer inhibitors developed, is in support of anticancer effects reported for all 3 major ingredients of the phytogenic product [ 13 , 27 , 45 ].…”
Section: Discussionmentioning
confidence: 94%
“…Carvacrol also has a range of benefits in addition to well documented antibacterial [ 17 ], anti–biofilm [ 18 , 19 ], antifungal [ 20 ], anticoccidial [ 21 ], anti-parasitic [ 22 ], antimalarial [ 23 ] and insecticide [ 24 , 25 , 26 ] abilities. In addition, carvacrol is a strong antitumor agent [ 27 ], especially against tumours related to sex hormones such as breast [ 28 ], cervical [ 29 ] and prostate. It alleviates oxidative and LPS induced stress [ 30 , 31 ], it is an anti-inflammatory and antioxidant in the respiratory system [ 32 ], strongly liver protective by slowing down liver fibrosis [ 33 ] and healing liver injury [ 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…The monoterpenes carvacrol, γ-terpinene, and thymol are known to disrupt the cell membrane and to influence several metabolic pathways, photosynthesis, cell respiration and mitosis [ 171 , 206 ]. However, there is not much known about the exact mechanism of carvacrol in plant metabolism [ 137 ], but it seems that this monoterpene deploys cytotoxic effects [ 191 , 207 ] that harm several plants. Similar to other monoterpenes, carvacrol has intense inhibitory effects on germination and seedling growth [ 179 ], suggesting that pathways other than photosynthesis are induced by carvacrol.…”
Section: Botanical Herbicidesmentioning
confidence: 99%